(3JaJjT GdeSGcf ai bGfhf GdELQGAGJ GdLfGFjI GdbWQi (B: s (3OQGSI ebGQfI (B/ s - (3SYO Mfja SYO eWQa GdOhSQis; (3YeQ eMeO SGde (B: s ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2015)
(3jJeJY GdaQO HMbhb CSGSjI gj (B"(3GdMbhb GdTNUjI(B" (3h GdCSGS ajgG GdMb ai GdMQjI h GdMb aj GdCef h GdScjfI(B. (3h jJaQY ef gPg GdMbhb (B"(3GdMb ai MQeI GdeScf(B" - (3ehVhY GdOQGSI(B. (3jMQU GdJTQjY GdOSJhQi h GdLfGFj Ydi MeGjI GdMb aj MQeI GdeScf(B: (3ZjQ Cfg ef GdWHjYj CdG jchf gPG GdMb eWdbkG h EfeG jLhR JbjjOg ef CLd eUdMI GdeLJeY(B: (3h dPdc jLhR ONhd GdeScf h JaJjTg h eQGbHJg aj MGdGJ eMOOI(B: (3h HeQGYGI GdTQhW GdJj jMOOgG GdJTQjY GdELQGFj(B. (3h jYfj ONhd GdeScf JNWi MOhOg h GdXghQ ajg(B: (3h gh jLhR aj MGdJj GdVQhQI h JfajP CeQ HGdbHV Ydi GdTNU(B: (3h gh YfUQ VQhQi aj ELQGA JaJjT GdeScf GdJj jbUO efg GdHMK aj eSJhOY GdSQ h gh ef ELQGAGJ GdJMbjbs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2015s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdbGfhf GdLfGFi GdbWQis; (3JaJjT GdeSGcfs; (3bGfhf GdELQGAGJ GdLfGFjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3cdjI GdMbhbs